KH. Abdul Karim Amrullah dan Gagasannya dalam Pengembangan Pendidikan Islam di Sumatera Barat - hasanah, uswatun; Afianah, Vina Nur; Salik, Mohamad (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
This article discusses about the ideas of KH Abdul Karim Amrullah in developing Islamic Education in West Sumatra. This is a kind of library research using descriptive-qualitative methode. The result of the research shows that KH. Abdul Karim Amrullah was one of the leading Muslim Intelectual who had been succesful in developing Islamic education especiallay in Minangkabau. Among of his thoughts were: 1) designing curriculum based on grade level 2) introducing learning methode which enable the students to develop their thinking skill, 3) training students to learn and practice in organization, 4) replacing the old Kitabs with the new ones which enable the students to develop their intelectuals as preparation to face the challenges of the times.